ANALISIS INDUSTRI PANGAN SUB SEKTOR INDUSTRI MAKANAN RINGAN KUE BANGKIT DAN BOLU (Dengan Menggunakan Strukture Conduct Performance/SCP) - Saka Putra; Syafril Basri; Eka Armas Pailis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aim is to determine the market structure, market behavior and market performance sponge cake industry. The data used is secondary data and primary data. This secondary data sourced from the Central Statistics Agency (BPS) and Pekanbaru City Department of Industry and Trade of the City of Pekanbaru. Primary data obtained from questionnaires distributed to 14 respondents in Pekanbaru. Methods of data analysis used in this research is descriptive analysis and quantitative analysis through theoretical approach-Product Structure-Performance. In this model, the variable used is the market share, concentration ratio, IHH, CLR, and PCM. The results revealed snack food industry and sponge cake rise in Pekanbaru city has its share of the market (market share) the highest of 15.2%. While businesses with market share (market share) that is equal to the lowest of 2.54%. Cake Industry in Pekanbaru city has a monopolistic market structure. Judging from the analysis of the capital-labor ratio (CLR), industry and sponge cake rise in Pekanbaru city included in labor intensive industries. Industry performance and sponge cake rise in Pekanbaru city based on the calculation of PCM that profit is not affected by the strength of the market share. The average value of 47.39% PCM where PCM highest value of 60% and the lowest rate of 28%.Keywords: Food Industry, Market Share, IHH, CLR, PCM